Implementasi Sistem Pendukung Keputusan Pemilihan Gadget Terbaik Dengan Metode Weighted Product - Fahrudin, Rifa'i, Heru Supriyono, ST. MSc. PhD (2016)
Choosing gadget is one of problem example where people choose a gadget depend on many factors or criteria based the different functions. This paper describe the result of last exam about the best decision supporting system of gadget selection with weighted product method is choosen because this method can determine quality value for each item, then it is continued by processing the grade to select the best alternative from several alternative. Its means that the best gadget according to customer's opinion, based on the certain criteria. By using this method the scoring is more accurate because based on criteria value and quality. Witch has fixed so it will get the better result forward the customer who will buys or just look for the reference are based price, brand, specification,and colors. Weighted product method is applied to select the best for selecting the best gadget based on study book and interview, beside that the writer used the quiz to the public community, such as students, students college, worker, ect. The result for this research is decision supporting program to recommend the best gadget selection which implemented on web-system so it can use online and the result of trial showed the procces can work well on browser used and other various browser with various screen resolution available.